Improving Students’ Vocabulary Mastery Through Audio Visual At Grade VIII Of SMP Negeri 2 Unaaha - Iin Wahyudi (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study was conducted on the bases of the preliminary study in SMP Negeri 2 Unaaha in which the researcher found that about 27,3% of the students in Grade VIIIb had lack ability in vocabulary. As an attempt to overcome the students’ difficulty in vocabulary mastery, the researcher/teacher gave audio visual. This study took the design of classroom action research because it was aimed at improving the existing condition in carrying out this study, the researcher acted as an observer. Design of this study was an action research the study was carried out in two cycles containing of four steps such as planning, action, observation and reflection. The subject of the study was all students of Grade VIIIb which consist of 22 students who registered in the academic year 2016/2017. The date were collected through three research istruments: vocabulary test, observation sheet, and field note. All of the date were analyzed, and the result of the analysis was compared to the criteria of success defined in this study to see whether yes or not they were achieved. The target of the study was students comprehended the vocabulary if minimally 75% of them got standard score 65. The result of the study showed that by giving audio visual could improve the students’ vocabulary mastery. It indicated that students at Grade VIIIb of SMP Negeri 2 Unaaha achieved the target on cycle II. It means that students’ vocabulary mastery could be improved by giving audio visual. In the cycle I, students who got standard score ≥65 only 54,6%. It means that not got standard indicator of successfulness. Then researcher continued the research at the cycle II for got standard score ≥65 only 81,9%. It means that got standard indicator of successfulness. This result indicated that by giving audio visual could improve students’ vocabulary mastery.